Polyandry in two South American harvester ants - Pol, Rodrigo Gabriel (2008)
Although monandry (single mating) is the ancestral state in social hymenopteran insects, effective mating frequencies greater than 2 have been confirmed for a fair amount of ant species: Cataglyphis cursor, the leaf-cutters of the genera Atta and Acromyrmex, army ants of the genera Eciton, Dorylus, Aenictus and Neivamyrmex, and some North American seed harvester species of the genus Pogonomyrmex. This last genus spreads throughout open arid habitats from Patagonia to southwestern Canada. Whereas some North American Pogonomyrmex species are thoroughly studied, we know much less about these ants in South America. The objective of this study was to estimate the effective mating frequency of Pogonomyrmex inermis and P. pronotalis, two Pogonomyrmex sensu stricto species from the central Monte desert of Argentina. A total of 477 P. pronotalis workers from 24 colonies and 402 P. inermis workers from 20 colonies were analyzed using six and four highly polymorphic microsatellites, respectively. The multilocus analysis revealed that all colonies were monogynous and all queens multiply-mated. The effective mating frequency was 8.75 and 6.52 for queens of P. pronotalis and P. inermis, respectively; those values increased up to 15.66 and 9.78, respectively, when corrected for sampling errors. This is the first demonstration that queens in at least some members of the South American Pogonomyrmex sensu stricto are strictly polyandrous, with mating numbers per queen at least as high as those previously found for North American species. We suggest that multiple mating probably arose early in the evolution of the genus Pogonomyrmex and may be the basis of its ecological success and wide distribution.